Sodstvo kot družbeni podsistem in javnost - Igličar, Albin (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2012)
The main social function of the judiciary ar: solving conflicts, protecting the interests (rights) of individuals and general (state) interests, social control, the judiciary in the function of a homeostatic mechanism and achieving system legitimacy and control of the executive branch of power. The public's perception of the judiciary and its confidence in the judicial system depends first and foremost on the public's notions of the tasks and competencies of the judicial authorities as they are formed in the public opinion. These notions and the related perception of the social functions of the judiciary are to a small extent formed on the basis of the individual personal experiences of participants in judicial proceedings and the experiences of others that these impart to their social environment. To a greater extent, the social perception and public opinion of the work of the courts depends on media reports, appearances of politicians and public appearances of representatives of the judiciary.
Keywords: delitev oblasti; pravosodje; sodniki; odločanje; javnost; javno mnenje